Evaluation of the Implementation of Adolescent Health Care Services (PKPR) at the Tanjung Priok Health Center in North Jakarta - Ira Midhawati; Anita Priska Purba; Sri Rahayu (PROMOTOR, 2026)
Adolescent-Friendly Health Services (Pelayanan Kesehatan Peduli Remaja/PKPR) is a strategic program aimed at improving adolescent health through promotive and preventive approaches. However, the implementation of PKPR at primary healthcare centers has not been fully optimal. This study aims to evaluate the implementation of PKPR services at Tanjung Priok Public Health Center, North Jakarta. A qualitative research approach was employed, with data collected through in-depth interviews, observations, and document review. Research informants included healthcare workers, PKPR program managers, and other related stakeholders. The findings reveal that the implementation of PKPR at Tanjung Priok Public Health Center has not been optimal, as indicated by limited human resources, insufficient specialized training related to PKPR, and suboptimal health promotion activities and adolescent involvement. In addition, cross-sectoral support and the utilization of facilities and infrastructure remain limited. These findings are consistent with the 2024 SNPKPR evaluation results, which reported an achievement score of 85.67%, the lowest in North Jakarta. Strengthening staff capacity, enhancing cross-sector collaboration, and developing innovative service strategies are necessary to improve the effectiveness of PKPR implementation in meeting adolescents’ health needs.